Injections of local anesthetics into the pharyngeal region reduce trapezius muscle tenderness - Weinschenk, Stefan; Hollmann, Markus W.; Göllner, Richard; Picardi, Susanne; Strowitzki, Thomas; Diehl, Leon Christopher; Hotz, Lorenz (Forschende Komplementärmedizin, 2016)
Background: Neck pain is a frequent reason for seeking medical advice. Neuroanatomical findings suggest a close connection between the pharynx and the trapezius region. Irritation of the pharynx may induce tenderness of this area. Specific tender points, called neck reflex points (NRPs), can be identified here with high reproducibility. We hypothesized that therapeutic local anesthesia (TLA; or neural therapy, NT) in the pharyngeal region can reduce tenderness in patients with therapy-resistant neck pain. Patients and Methods: 17 consecutive female patients with chronic cervical pain and positive trapezius NRPs received bilateral injections of 0.5 ml 1% procaine into the palatine velum. The NRPs were assessed using a 3-level pain index (PI = 0, 1, or 2) before and 3-5 min after each injection. Results: We found a significant reduction in tenderness of the NRP of the trapezius region (NRP C7) immediately after TLA/NT. 30 positive NRPs were found before therapy and only 13 after therapy (p < 0.01). The average PI of the NRP C7 was 1.24 ± 0.77 before and 0.35 ± 0.59 after therapy (right side), and 1.34 ± 0.59 before and 0.59 ± 0.69 after therapy (left side). The pre- and post-therapy PI values were significantly different on both the right and left sides of the trapezius region (p < 0.01). No adverse effects were observed. Conclusions: Pharyngeal irritation may induce and maintain therapy-resistant cervical pain in patients with chronic pharyngeal disease. These patients could benefit from remote TLA/NT injections in the pharyngeal region.